Unsaturated edge-anchored Ni single atoms on porous microwave exfoliated graphene oxide for electrochemical CO2 - Cheng, Yi; Zhao, Shiyong; Li, Haobo; He, Shuai; Veder, Jean-Pierre; Johannessen, Bernt; Xiao, Jianping; Lu, Shanfu; Pan, Jian; Chisholm, Mattew F.; Yang, Shi-Ze; Liu, Chang; et al. (Applied catalysis. B, Environmental, 2019)
[Display omitted] •3D porous graphene with high loading (6.9 wt%) of single atom Ni was produced.•High performance in electrochemical CO2 reduction was achieved.•Single atom and nanopores revealed by electron microscopy and X ray absorption.•DFT Simulation reveals the mechanism and confirms role of edge anchored single atoms. Supported single atom catalysts (SACs), emerging as a new class of catalytic materials, have been attracting increasing interests. Here we developed a Ni SAC on microwave exfoliated graphene oxide (Ni-N-MEGO) to achieve single atom loading of ∼6.9 wt%, significantly higher than previously reported SACs. The atomically dispersed Ni atoms, stabilized by coordination with nitrogen, were found to be predominantly anchored along the edges of nanopores ( < 6 nm) using a combination of X-ray absorption spectroscopy (XAS) and aberration-corrected scanning transmission electron microscopy (AC-STEM). The Ni-N-MEGO exhibits an onset overpotential of 0.18 V, and a current density of 53.6 mA mg−1 at overpotential of 0.59 V for CO2 reduction reaction (CO2RR), representing one of the best non-precious metal SACs reported so far in the literature. Density functional theory (DFT) calculations suggest that the electrochemical CO2-to-CO conversion occurs more readily on the edge-anchored unsaturated nitrogen coordinated Ni single atoms that lead to enhanced activity toward CO2RR.